Pengaruh Berbagi Informasi terhadap Kinerja Rantai Pasok dengan Kepercayaan sebagai Variabel Mediasi - Alicia Delfinia Azahra; Moh Mukhsin; Diqbal Satyanegara (CV. ITTC INDONESIA, 2025)
This study examines how information sharing drives supply chain performance improvements, with trust serving as a mediating variable. Data collection involved questionnaires and literature review, targeting 77 rice store respondents in Tangerang Regency. The research employed purposive sampling to ensure appropriate respondent characteristics, and utilized SEM-PLS (Structural Equation Modeling based on Partial Least Squares) for quantitative analysis. The findings revealed four key insights: First, information sharing activities showed a significant positive relationship with supply chain performance. Second, information sharing demonstrated a clear positive impact on building trust. Third, trust levels proved to substantially enhance supply chain performance. Fourth, the analysis confirmed trust's role as a mediating variable linking information sharing activities to supply chain performance outcomes